A Comprehensive View of Human Chromosome 1 - White, Peter S.; Sulman, Erik P.; Porter, Christopher J.; Matise, Tara C. (Genome Research, 1999)
Comprehensive representations of human chromosomes combining diverse genomic data sets, localizing expressed sequences, and reflecting physical distance are essential for disease gene identification and sequencing efforts. We have developed a method (CompView) for integrating genomic information derived from available cytogenetic, genetic linkage, radiation hybrid, physical, and transcript-based mapping approaches. CompView generates chromosome representations with substantially higher resolution, coverage, and integration than current maps of the human genome. The CompView process was used to build a representation of human chromosome 1, yielding a map with >13,000 unique elements, an effective resolution of 910 kb, and a marker density of 50 kb. CompView creates comprehensive and fully integrated depictions of a chromosome's clinical, biological, and structural information.